(3x-5)+(2x)+(x)=139

Simple and best practice solution for (3x-5)+(2x)+(x)=139 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-5)+(2x)+(x)=139 equation:


Simplifying
(3x + -5) + (2x) + (x) = 139

Reorder the terms:
(-5 + 3x) + (2x) + (x) = 139

Remove parenthesis around (-5 + 3x)
-5 + 3x + (2x) + (x) = 139
-5 + 3x + (2x) + x = 139

Combine like terms: 3x + (2x) = 5x
-5 + 5x + x = 139

Combine like terms: 5x + x = 6x
-5 + 6x = 139

Solving
-5 + 6x = 139

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 6x = 139 + 5

Combine like terms: -5 + 5 = 0
0 + 6x = 139 + 5
6x = 139 + 5

Combine like terms: 139 + 5 = 144
6x = 144

Divide each side by '6'.
x = 24

Simplifying
x = 24

See similar equations:

| 5n=440 | | 3(1.9-x)=4.5 | | 3(5c)+8=21 | | (-5u^2+7u-3)-(4u^2-2u+3)+(2u^2+2u-3)= | | 2x+(3x+5)=6 | | -3(3y+2)+9=-6 | | 180-x+11=3x+1 | | 5.1(6x+.07)-4.2=-1.5x+8.2 | | 3x^4+4x^3-36x^2+84=0 | | 3[60-s]-2s=105 | | 49=42x+4x^2 | | -9y+-6+9=-6 | | 6x-3(4x+5)=16 | | 12x+48=10x-4 | | 3x=7(4.322580645)-2 | | 3x-4+x+3x-4=55 | | 70=2x-10 | | 24m+42n-30= | | 3(10.5+-0.25y)=7y-2 | | 3x-4+x+3x-4= | | 10-6x+3x+2=57 | | 3=4+5y | | 9(10.5+-0.25y)=4x+1 | | 4(u+2)-7u=-10 | | 2x-3x-1=-5 | | 61-c=9 | | 3x^2-x^2+1600=0 | | 10(w+3)-14=66 | | 26=3(10.5+-0.25y)-2y | | -2(j-3)=-2j-6 | | 4w^2+21w-21=0 | | 6x-83=-47 |

Equations solver categories